Operatory kompozycji i mnożenia pomiędzy różnymi przestrzeniami Orlicza - Chawziuk, Tadeusz (My University, 2018)
Bada się operatory kompozycji i mnożenia między różnymi przestrzeniami Orlicza narzędziami teorii przestrzeni Orlicza (metoda wewnętrzna) lub w języku wzajemnego zawierania się ogólniejszych przestrzeni Musielaka-Orlicza (metoda zewnętrzna). Analizowana jest ciągłość, jednakowa absolutna ciągłość, zwartość, surjektywność, domknięty obraz, skończony rząd i własność Fredholma. Udało się udowodnić równoważne warunki dla tych własności i rozmaite warunki dostateczne lub konieczne. Uwzględniają one charakterystyki funkcji generujących przestrzenie Orlicza, przestrzeni miary, transformacji indukującej operator kompozycji lub funkcji indukującej operator mnożenia. Rozważane są ogólne, bezatomowe i czysto atomowe przestrzenie miary i odpowiednio dowodzone są twierdzenia. Rozprawa składa się z pięciu rozdziałów. Pierwszy podaje podstawowe pojęcia. Drugi bada ciągłość metodą wewnętrzną. Trzeci bada ciągłość i surjektywność metodą zewnętrzną. Czwarty dotyczy jednakowej absolutnej ciągłości i zwartości. Piąty za pomocą obu metod bada domkniętość obrazu, skończony rząd i własność Fredholma.

We analyze composition and multiplication operators between distinct Orlicz spaces with tools available within Orlicz space theory (the internal method) and in terms of inclusions between more general Musielak-Orlicz spaces (the external method). Continuity, uniform absolute continuity, compactness, surjectivity, closed range, finite rank, and Fredholmness of the operators are examined. It was possible to establish equivalent conditions for these properties, as well as various sufficient or necessary conditions. They involve properties of the convex functions generating Orlicz spaces, of the underlying measure spaces, and of the transformation between measure spaces inducing the composition operator or the real-valued function on a measure space inducing the multiplication operator. General measure spaces, non-atomic, and purely atomic measure spaces are considered, and the theorems are proved accordingly. The dissertation consists of five chapters. Thefirst presents basic notions and conventions used later. The second tackles continuity of the operators via the internal method. The third chapter applies the external method to continuity and surjectivity. The fourth privides theorems on uniform absolute continuity and compactness. The fifth deals with closed range, finite rank, and Fredholmness of the operators, employing the internal and the external method.
Composition and Multiplication Operators between Distinct Orlicz Spaces
Wydział Matematyki i Informatyki
Keywords: Operator kompozycji; operator mnożenia; przestrzenie Orlicza; ciągłość; zwartość; Orlicz spaces; Composition operator; multiplication operator; continuity; compactness